Interpreting the legacy: John Neihardt and Black Elk speaks - Holloway, Brian, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
Ambitious and provocative, Interpreting the Legacy: John Neihardt and Black Elk Speaks is a new study of the classic spiritual text that is sure to spark debate. Neihardt's work has recently been critiqued by scholars who maintain that the author filtered and corrupted Black Elk's teachings through a European spiritual and political lens. In this book, Brian Holloway offers a rather different view, making a convincing case that Neihardt quite consciously attempted to use his literary craftsmanship to provide the reader with direct and immediate access to the teachings of the Oglala elder. Using Neihardt's original handwritten notes and early manuscript drafts, Holloway demonstrates the poet's careful and deliberate re-creation of Black Elk's spiritual world in order to induce a transcendent experience in the reader. Through exhaustive research into Neihardt's biographical materials, published philosophical and metaphysical writings, and volumes of taped lectures, Holloway examines the sources of the book's production as well as the reactions to and the implications of Neihardt's literary portrayal of the spiritual world of the Oglala.--Book jacket.
Preface to the Paperback Edition -- Preface and Acknowledgments -- Introduction -- 1. Seeing Black Elk Speaks -- 2. Others Speak -- 3. The Sacred Collaboration -- 4. The Art of Black Elk Speaks -- 5. Sincerest Flattery -- 6. Black Elk Speaks Today.
Originally published in 2003.
Keywords: Oglala Indians -- Biography; Oglala Indians -- Religion; Black Elk, 1863-1950. Black Elk speaks; Lakota Indians; Neihardt, John G., 1881-1973